Effects of Prepayment Regulations on Termination of Subprime Mortgages - Steinbuks, Jevgenijs (Elsevier, 2015)
Because of their higher interest rates, subprime mortgages are subject to substantial prepayment risk as borrowers who succeed in improving their creditworthiness systematically prepay leaving those with higher credit risk in the mortgage pool. Lenders anticipated this problem and attached substantial prepayment penalties to subprime mortgages. Some state governments responded with regulations that banned prepayment penalties. This created a natural experiment in which the effects of prepayment penalties on the supply and performance of endorsed mortgages can be evaluated. Ho and Pennington Cross (2008) have demonstrated that these regulations reduced the supply of mortgage credit. In this paper, the effect of prepayment penalty restrictions on the performance of endorsed subprime mortgages is tested. Theory predicts that the restrictions should raise prepayment and lower default. The empirical results strongly confirm the first prediction while the effects on default have the correct sign but lack significance.